2020
DOI: 10.1007/s00262-020-02543-6
|View full text |Cite
|
Sign up to set email alerts
|

Significant association between tumor mutational burden and immune-related adverse events during immune checkpoint inhibition therapies

Abstract: More than 2000 immuno-oncology agents are being tested or are in use as a result of the cancer immunotherapy revolution. Manipulation of co-inhibitory receptors has achieved tumor eradication in a minority of patients, but widespread immunerelated adverse events (irAEs) compromised tolerance to healthy self-tissues in the majority. We have proposed that a major mechanism of irAEs is similar to a graft-versus-malignancy effect of graft-versus-host disease. To verify our hypothesis, we retrieved post-marketing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…Whole exome sequencing of the mutagenized YUMM1.7-CM clone revealed that nearly 15% of the acquired base substitutions, cause amino acid changes that are likely to contribute to neoantigen formation and improved engagement of immune system. The notion that neoantigen formation enhances antitumor immunogenicity and improves responses to ICB therapy is supported by clinical outcomes demonstrating that tumors with high mutational loads are more likely to respond to ICB therapies (2,37), rendering the mutational burden an important, albeit imperfect predictor of response to ICB (3,4,38,39). Examples from the clinic include subpopulations of colon cancer patients with DNA mismatch repair deficiency characterized by high tumoral mutation burden and elevated neoantigens, which have shown high response rates to anti-PD-1 checkpoint blockade (7,40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Whole exome sequencing of the mutagenized YUMM1.7-CM clone revealed that nearly 15% of the acquired base substitutions, cause amino acid changes that are likely to contribute to neoantigen formation and improved engagement of immune system. The notion that neoantigen formation enhances antitumor immunogenicity and improves responses to ICB therapy is supported by clinical outcomes demonstrating that tumors with high mutational loads are more likely to respond to ICB therapies (2,37), rendering the mutational burden an important, albeit imperfect predictor of response to ICB (3,4,38,39). Examples from the clinic include subpopulations of colon cancer patients with DNA mismatch repair deficiency characterized by high tumoral mutation burden and elevated neoantigens, which have shown high response rates to anti-PD-1 checkpoint blockade (7,40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Although a limited transformation is too weak in itself to instigate a tumor eradicating T-cell attack, with immune checkpoint blockade T cells are more effective against “altered self” resulting in better OS [ 45 ]. Not unexpectedly, a significant positive correlation was found between the reporting odds ratio (ROR) of reporting an irAE during anti-CTLA-4, anti-PD-1, and anti-CTLA-4/anti-PD-1 immune combination therapies and the corresponding TMB in 7677 patients across 19 cancer types [ 46 ]. Consistent with this, Berner et al demonstrated in NSCLC that T cells recognize and target shared tumor and skin antigens during ICI therapy resulting in autoimmune-mediated skin toxicity and tumor regression [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that TMB in dMMR/MSI-H CRCs is significantly higher than that in pMMR/MSI-L CRCs ( 48 , 67 69 ), and an increased amount of TMB in dMMR/MSI-H tumours can result in a 20-time higher rate of mutation and a stronger immune response than pMMR/MSI-L tumours ( 52 , 53 , 58 ), which are reflected in the very different composition and function of immune infiltrates in the TIME ( 70 73 ). Therefore, TMB appears to be an important biomarker for patients with dMMR/MSI-H CRC in response to anti-PD-1 therapy ( 68 , 74 77 ).…”
Section: The Possible Mechanisms Leading To a Distinct Therapeutic Efmentioning
confidence: 99%